2022
DOI: 10.2967/jnumed.121.263598
|View full text |Cite
|
Sign up to set email alerts
|

Distinction of Lymphoma from Sarcoidosis on18F-FDG PET/CT: Evaluation of Radiomics-Feature–Guided Machine Learning Versus Human Reader Performance

Abstract: Sarcoidosis and lymphoma often share common features on 18 F-FDG PET/CT, such as intense hypermetabolic lesions of lymph nodes and multiple organs. We aimed at developing and validating radiomics signatures to differentiate sarcoidosis from Hodgkin (HL) and diffuse large B-cell (DLBCL) lymphoma. Methods: We retrospectively collected 420 patients (169 sarcoidosis, 140 HL and 111 DLBCL) who underwent a pretreatment 18 F-FDG PET/CT at the University Hospital of Liege. The studies were randomly distributed to 4 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A study differentiates sarcoidosis and lymphomas with seven different feature selection approaches and four different ML classifiers. At the lesion level, they found highly accurate signatures to create models to differentiate cancer vs. sarcoidosis (AUC 0.94) and Hodgkin vs. diffuse large B-cell lymphoma (AUC 0.95) ( 36 ). In a more extensive cohort retrospective study ( 37 ), the researchers used a CNN to automatically locate and classify PET uptake patterns in lung cancer and lymphoma.…”
Section: Resultsmentioning
confidence: 99%
“…A study differentiates sarcoidosis and lymphomas with seven different feature selection approaches and four different ML classifiers. At the lesion level, they found highly accurate signatures to create models to differentiate cancer vs. sarcoidosis (AUC 0.94) and Hodgkin vs. diffuse large B-cell lymphoma (AUC 0.95) ( 36 ). In a more extensive cohort retrospective study ( 37 ), the researchers used a CNN to automatically locate and classify PET uptake patterns in lung cancer and lymphoma.…”
Section: Resultsmentioning
confidence: 99%
“…However, both sarcoid and lymphoma are FDG avid and the distinction between benign and malignant disorders on the basis of a PET scan is difficult. Current reports have shown that this imaging technique can correctly characterize sarcoidosis and lymphoma lesions with very good performance, sometimes supported by machine learning combined with radiomics [ 25 ]. Despite the above, histopathology remains to date the sarcoidosis diagnosis cornerstone, given that correct classification based on imaging can create a diagnostic challenge and misclassification it is still not infrequent and has important consequences [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…de Jesus et al [ 77 ] reported that the ML model with the gradient boosting algorithm using PET/CT radiomics had a significantly higher AUC in distinguishing DLBCL and follicular lymphoma according to SUVmax (AUC:0.86 vs. 0.79, p < 0.01). Lovinfosse et al [ 78 ] also showed that the ML model with the RF algorithm using clinical data and PET-radiomics had good performance in differentiating DLBCL from HD, with an AUC of 0.95. Further, the authors showed that the constructed ML model with the RF algorithm had good performance in differentiating malignant lymphoma and sarcoidosis, with an AUC of 0.94.…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...mentioning
confidence: 99%